VIDEOTHORACOSCOPY FOR CLOTTED HEMOTHORAX IN PATIENTS WITH PENETRATING CHEST TRAUMA - O. V. Voskresensky; Sh. N. Daniyelian; M. M. Abakumov (Неотложная медицинская помощь)
BACKGROUND. Clotted hemothorax is the most common complication of the chest injury requiring surgical treatment in most patients.MATERIAL AND METHODS. Videothoracoscopy was performed in 51 patients with complications of penetrating chest trauma in 2011–2012. Clotted hemothorax occured in 27 cases (52.9%).RESULTS. It was found that the main cause of this complication was inadequate pleural drainage effect. Clotted hemothorax developed after drainage of the pleural cavity and primary surgical debridement in 12 patients (44.4%), in 8 patients (29.6%) after atypical thoracotomy and in 7 patients (25.9%) after typical thoracotomy. The average interval between operations was 8.1±5.0 days.CONCLUSION. The best results of treatment for clotted hemothorax were achieved under the early detection of clotted hemothorax in case of thoracoscopic evacuation in the range from 3 to 7 days (4.7±2.1). Videothoracoscopy performed more than 7 days after detection may increase the volume of surgery, cause significant complications, and considerably prolong treatment.